Overcoming Barriers in Neurosurgical Education: A Novel Approach to Practical Ventriculostomy Simulation. Issue 3 (11th September 2022) - Amini, Amir; Zeller, Yannic; Stein, Klaus-Peter; Hartmann, Karl; Wartmann, Thomas; Wex, Cora; Mirzaee, Elyas; Swiatek, Vanessa M.; Saalfeld, Sylvia; Haghikia, Aiden; Dumitru, Claudia A.; Sandalcioglu, I. Erol; et al.
Abstract : BACKGROUND: In the high-risk, high-stakes specialty of neurosurgery, traditional teaching methods often fail to provide young residents with the proficiency needed to perform complex procedures in stressful situations, with direct effects on patient outcomes. Physical simulators provide the freedom of focused, hands-on training in a more controlled environment. However, the adoption of simulators in neurosurgical training remains a challenge because of high acquisition costs, complex production processes, and lack of realism. OBJECTIVE: To introduce an easily reproducible, cost-effective simulator for external ventricular drain placements through various ventriculostomy approaches with life-like tactile brain characteristics based on real patients' data. METHODS: Whole brain and skull reconstruction from patient's computed tomography and MRI data were achieved using freeware and a desktop 3-dimensional printer. Subsequently, a negative brain silicone mold was created. Based on neurosurgical expertise and rheological measurements of brain tissue, gelatin in various concentrations was tested to cast tactilely realistic brain simulants. A sample group of 16 neurosurgeons and medical students tested and evaluated the simulator in respect to realism, haptics, and general usage, scored on a 5-point Likert scale. RESULTS: We saw a rapid and significant improvement of accuracy among novice medical students. All participants deemed the simulator as highly realistic, effective, and superior to conventional training methods. CONCLUSION: We were able to demonstrate that building and implementing a high-fidelity simulator for one of the most important neurosurgical procedures as an effective educational and training tool is achievable in a timely manner and without extensive investments.